(untitled) (Raparin Journal of Humanities (RJH), 2025)
In this study, the researchers focused on investigating the role of Kurdish news channels’ television programs in montoring government affairs from the perspective of Kurdish media elites. It is obvious, the Kurdistan Regional Government (KRG) has experienced numerous crises that have had a significant impact on citizens’ lives. The main objective of this study is to determine the extent to which television programs play a role in monitoring government affairs, as perceived by the media elite. The researchers aimed to identify the factors that affect the application of the watchdog function in television programs. The study utilized a descriptive research method, and data were collected through a survey form. The results of the study revealed that a majority of the respondents sometimes watched television programs about government affairs, and their motivation was to gain information about government decisions. It was also found that, according to the majority of the media elite, television programs played a moderate role in monitoring government. Additionally, the study identified barreiers of this normative role such as, political obstacles, restrictions on freedom of expression, and lack of access to information as the main factors that hindered the effectiveness of monitoring role in television programs in KRI.